DIFICULTADES DE LA INCLUSIÓN LABORAL DE PERSONAS CON DISCAPACIDAD DESDE LA PERSPECTIVA DE GÉNERO - Sánchez Trigueros, Carmen (2022)
Women with disabilities are subject to multidiscrimination that significantly conditions their access to employment and working conditions. The gender pay gap affects this segment incisively. Women with disabilities receive a lower salary than men in the group and women without disabilities. In addition to economic and professional disadvantages, women with disabilities also suffer more gender-based violence. The latest Macro-survey on Violence against Women defines 6 types of gender violence, and the prevalence of intimate partner violence throughout life among women with accredited disabilities is higher than among women without accredited disabilities in all cases. Thus, 20.7 % of women with a certified disability have suffered physical or sexual violence from a partner compared to 13.8 % of women without a certified disability. 40.4 % of women with a certified disability have suffered some type of violence in their partner compared to 31.9 % of women without a certified disability. 17.5 % of women with disabilities who have suffered VFSEM from a partner say that their disability is a consequence of partner violence. This percentage rises to 23.4 % among women with disabilities who have suffered physical sexual violence from a partner.